Building Oral Literature and National Character through Creative and Productive Learning Models as an Innovative Effort to Develop Students' Writing Skills - Sakdiah Wati (AL-ISHLAH: Jurnal Pendidikan, 2024)
The Productive Creative Learning model is a strategic framework integrating various methodologies to enhance teaching and learning effectiveness. It aims to inspire students to create innovative works, necessitating subtle instruction in literature and a shift from traditional paradigms. This model promotes knowledge acquisition, meaningful discussions, and the production of innovative literary works by both students and lecturers. This quantitative study in education evaluates the efficacy of this teaching paradigm, specifically to enhance creative writing skills. Using Gall and Borg's (2003) development approach, researchers follow a three-stage process: gathering information through literature and field studies, developing the model via trials and improvements, and validating it through experimental design. This flexible approach suits social sciences and language studies, accommodating diverse behaviors and language usage patterns. The research targets Indonesian Language Education students in the 4th and 5th semesters at FKIP Universitas Muhammadiyah Palembang, aiming to develop a model that: (1) aligns with curriculum objectives, (2) functions with or without lecturers, and (3) enhances creative writing skills. Activities include observing quasi-experimental classes, selecting short stories as teaching materials, preparing, testing, evaluating, and revising learning models. Effectiveness is evaluated using gain and t-tests. The Productive Creative Learning Model, akin to a literary studio, is an effective approach for teaching literature, complementing external literary organizations with its beneficial principles.